Religious Coping and Posttraumatic Growth in Women After Perinatal Loss In Indonesia: Literature Review - Suffah, Fasya Khalida; Kilis, Grace (Universitas Negeri Padang, 2024)
Perinatal loss, defined as the death of a fetus or infant either during pregnancy or shortly after birth, is an event experienced by women globally. Women who experience perinatal loss often undergo significant psychological challenges, including grief, depression, and anxiety. However, amidst this adversity, some women exhibit Posttraumatic Growth, wherein they experience positive psychological changes as a result of their struggle with trauma. Several factors influence posttraumatic growth, including religious coping which refers to the use of religious or spiritual beliefs and practices to manage stress and adversity. In Indonesia, where religion holds significant importance, coping mechanisms based on religion show potential in promoting posttraumatic growth. The research method in this study used the seven-step guideline for carrying a review by De Klerk & Pretorius (2019), that explores mechanisms through which religious coping influences posttraumatic growth in this population. In total, 159 articles were collected and 15 articles met the eligibility criteria and were chosen for thorough analysis. The results indicates that RC serves as an adaptive strategy by reframing it as a positive aspect and transforming its meaning,leading to positive psychological transformations conducive to posttraumatic growth.